2017
DOI: 10.1016/j.jpba.2017.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of stereoselective drug interactions with serum proteins by high-performance affinity chromatography: A historical perspective

Abstract: The interactions of drugs with serum proteins are often stereoselective and can affect the distribution, activity, toxicity and rate of excretion of these drugs in the body. A number of approaches based on affinity chromatography, and particularly high-performance affinity chromatography (HPAC), have been used as tools to study these interactions. This review describes the general principles of affinity chromatography and HPAC as related to their use in drug binding studies. The types of serum agents that have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 147 publications
(287 reference statements)
0
20
0
Order By: Relevance
“…Plasma proteins are capable of interacting with about 43% of the 1500 drugs most commonly used in clinical practice [1,2]. Moreover, the drugs frequently show a high affinity for these proteins (about 90% or more of the administered dose binds to plasma proteins) [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma proteins are capable of interacting with about 43% of the 1500 drugs most commonly used in clinical practice [1,2]. Moreover, the drugs frequently show a high affinity for these proteins (about 90% or more of the administered dose binds to plasma proteins) [3].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the drugs frequently show a high affinity for these proteins (about 90% or more of the administered dose binds to plasma proteins) [3]. Consequently, the interaction between drugs and plasma proteins is quite significant, which is reflected in the biological action of drugs [1,2]. It should be noted that the interactions established between proteins and drugs are reversible, since the purpose is to transport the compounds to the different tissues in order to achieve their biotargets.…”
Section: Introductionmentioning
confidence: 99%
“…Various analytical techniques that have been used to characterize biomolecular interactions. Some of these techniques include affinity-based separation techniques, which represent the major domain of affinity chromatography, [4][5][6] and affinity capillary electrophoresis [7][8][9] as well as equilibrium dialysis, which is still interesting and widely used especially in drug-protein interaction studies [10][11][12]. On the other hand, biochemical and biophysical techniques are attractive and developed dramatically to be the first choice in studying biomolecular interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the number of publications describing the use of protein-based CSPs has been decreasing over the years [ 117 , 136 ]. Binding affinity studies between drugs and proteins and drug-protein interactions were also found [ 137 , 138 , 139 ].…”
Section: Chiral Stationary Phases: Recent Developmentsmentioning
confidence: 99%